Factors Affecting Credit Risk: An Empirical Study of the Jordanian Commercial Banks - Al-abedallat, Abedalfattah Zuhair (European Scientific Journal, ESJ, 2016)
The problem of the study shows that various Banks suffer from many types of banking risks. This has significantly affected banks' profits. The credit risk is considered to be the major risks to commercial banks. Also, the study aimed to identify the various factors that are affecting credit risk. The study findings shows that there is significant statistical impact of the factors (the efficiency of workers in the banking credit, the instructions of the Central Bank, and the credit policy of the bank) on the credit risks in the Jordanian commercial banks. The study rejected the null hypotheses and accepted the alternative hypotheses for the main hypotheses and three subhypothesis. The study recommended that the central bank should increase their oversight on the credit granted by the commercial banks. Also, the commercial banks should establish a department of risk management, and make diversification in the credit facilities so as to reduce the credit risk.